The Universally Conserved ATPase YchF Regulates Translation of Leaderless mRNA in Response to Stress Conditions - Landwehr, Victoria; Milanov, Martin; Angebauer, Larissa; Hong, Jiang; Jüngert, Gabriela; Hiersemenzel, Anna; Siebler, Ariane; Schmit, Fränk; Öztürk, Yavuz; Dannenmaier, Stefan; Drepper, Friedel; Warscheid, Bettina; et al. (Frontiers in Molecular Biosciences, 2021)
The universally conserved P-loop GTPases control diverse cellular processes, like signal transduction, ribosome assembly, cell motility, intracellular transport and translation. YchF belongs to the Obg-family of P-loop GTPases and is one of the least characterized member of this family. It is unique because it preferentially hydrolyses ATP rather than GTP, but its physiological role is largely unknown. Studies in different organisms including humans suggest a possible role of YchF in regulating the cellular adaptation to stress conditions. In the current study, we explored the role of YchF in the model organism Escherichia coli. By western blot and promotor fusion experiments, we demonstrate that the YchF levels decrease during stress conditions or when cells enter stationary phase. The decline in YchF levels trigger increased stress resistance and cells lacking YchF are resistant to multiple stress conditions, like oxidative stress, replication stress or translational stress. By in vivo site directed cross-linking we demonstrate that YchF interacts with the translation initiation factor IF3 and with multiple ribosomal proteins at the surface of the small ribosomal subunit. The absence of YchF enhances the anti-association activity of IF3, stimulates the translation of leaderless mRNAs and increases the resistance against the endoribonuclease MazF, which generates leaderless mRNAs during stress conditions. In summary, our data identify YchF as a stress-responsive regulator of leaderless mRNA translation.